Дослідження ефективності диспергування молочного жиру в гомогенізаторі пульсаційного типу - Паляничка, Надія Олександрівна; Червоткіна, Олександра Олександрівна; Ковальов, Олександр Олександрович; Ялпачик, Володимир Федорович; Palianychka, Nadiia; Chervotkina, Oleksandra; Kovalov, Oleksandr; Yalpachyk, Volodymyr (Запоріжжя : ТДАТУ, Видавничий дім «Гельветика», 2025)
UA: Ця робота присвячена дослідженню теми диспергування молочного жиру шляхом гомогенізації. Встановлено, що існуюче технологічне обладнання для гомогенізації має дуже високі показники енерговитрат на процес, що в умовах сьогодення є суттєвим недоліком. За підсумками дослідження встановлено, що найбільш перспективним обладнанням для досягнення високої якості готового продукту за низьких енерговитрат є пульсаційний гомогенізатор. Було здійснено аналіз ефективності диспергування молочного жиру в пульсаційному гомогенізаторі молока, що дало можливість виявити чинники та сили, які впливають на якість гомогенізації, а отже, регулювати цей технологічний процес у виробничих умовах. Експериментальні дослідження показали, що середній діаметр жирових кульок молока після гомогенізації в пульсаційному гомогенізаторі становить 0,8 мкм, що цілком відповідає вимогам сьогодення. EN: This work is devoted to the study of the topic of milk fat dispersion by homogenization. The process of dispersion by homogenization is currently quite widespread, it is widely used in many industries, including food and processing. In the technological line of milk processing and dairy product production, the homogenization process is one of the most important, since dispersion affects the taste and sensory characteristics of the finished product. Valve-type homogenizers have become widespread in food industry enterprises, however, in today's conditions, their use is very inefficient and costly, since such homogenizers use a lot of electricity. The conducted analytical studies allowed us to establish a promising type of homogenizer – pulsating, which allows us to significantly reduce electricity consumption for the homogenization process, without losing the quality of the finished product. A study of the efficiency of milk fat dispersion in a pulsating milk homogenizer was conducted, which allowed us to establish the factors and forces that affect the quality of homogenization, which will subsequently allow us to regulate this technological process in production conditions. The conducted experimental studies showed that to obtain the maximum degree of homogenization Hm = 5 with minimal specific energy consumption Epit = 0.83 J/kg, it is necessary to create the following conditions: the amplitude of the piston-hammer oscillations is 10…12 mm, the oscillation frequency is 55…59 Hz and the milk supply in the pulsating homogenizer is 1800…2000 kg/h, which in turn indicates the efficiency of using the pulsating homogenizer in dairy processing lines. It was also established that the average diameter of milk fat globules is 0.80 μm. At the same time, the uniformity of the fractional composition after processing in the experimental homogenizer is no less than that of the reference valve homogenizer, which fully meets today's requirements.
Research on the efficiency of milk fat dispersion in a pulsation-type homogenizer
Keywords: диспергування; якість; пульсаційний гомогенізатор; молочний жир; ступінь гомогенізації; ефективність; енергоємність; dispersion; quality; pulsating homogenizer; milk fat; degree of homogenization; efficiency; energy consumption